The influence of tahajjud prayer on cortisol hormone and spiritual dimensions: Holistic study - Aulia, Agustina Pretty; Shalsabillah, Naila Riezqi; Amiruddin, Muhammad; `Inayatullah, Muhammad; Amiruddin, Atikah (Maliki Interdisciplinary Journal, 2025)
This study discusses the concept and significance of tahajjud therapy in the context of tarbiyah, which is a mental education process to strengthen faith in Allah SWT. Tahajjud therapy, as a form of evening worship, has great potential in improving the quality of an individual's faith and monotheism. The tahajjud prayer in Islam is an evening prayer that follows the sunnah of the Prophet Muhammad SAW. This practice has a positive impact on an individual's physical and spiritual health. Physically, tahajjud prayer maintains fitness and manages stress through physical movement and the production of the hormone cortisol. In addition, this study examines the relationship between tahajjud prayer and the hormone cortisol in stress management, highlighting the positive impact of tahajjud therapy on physical and mental health. This study uses a literature review methodology. In this study, we explore various aspects of tahajjud therapy, including prayer content which plays an important role in educating and strengthening a servant's obedience to the Creator. With a deep understanding of this practice, it is hoped that this study can provide useful insights for individuals who wish to deepen their spiritual connection with Allah SWT and strengthen their belief in Iman and Islam. It is hoped that individuals can utilize tahajjud therapy as a means for a spiritual approach and holistic well-being.